2018
DOI: 10.3390/ijms19051414
|View full text |Cite
|
Sign up to set email alerts
|

The DNA Methylome and Association of Differentially Methylated Regions with Differential Gene Expression during Heat Stress in Brassica rapa

Abstract: Cytosine DNA methylation is a critical epigenetic mechanism in the silencing of transposable elements, imprinting and regulating gene expression. However, little is known about the potential role of mC in response to heat stress. To determine and explore the functions of the dynamic DNA methylome during heat stress, we characterized single-base resolution methylome maps of Brassica rapa and assessed the dynamic changes of mC under heat stress using whole genome bisulfite sequencing. On average, the DNA methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 92 publications
5
43
0
Order By: Relevance
“…The exact physiological significance of this change was not explored, and the effects of methylation depend on which sequences and which genes experience changes in methylation, but differences in DNAmethylation are likely to reflect physiological effects and/or have physiological consequences. Previous reports have shown differences in DNA methylation and cytogenetic changes induced in plants at similar IR exposure rates (Kovalchuk et al, 2003) and changes in DNA methylation have been reported to have significant physiological consequences in other contexts (Liu et al, 2018). The results reported here are, therefore, consistent with other suggestions that changes at sub-cellular levels of biological organization, e.g., cytogenetic and physiological, can be induced at the dose rates used here.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The exact physiological significance of this change was not explored, and the effects of methylation depend on which sequences and which genes experience changes in methylation, but differences in DNAmethylation are likely to reflect physiological effects and/or have physiological consequences. Previous reports have shown differences in DNA methylation and cytogenetic changes induced in plants at similar IR exposure rates (Kovalchuk et al, 2003) and changes in DNA methylation have been reported to have significant physiological consequences in other contexts (Liu et al, 2018). The results reported here are, therefore, consistent with other suggestions that changes at sub-cellular levels of biological organization, e.g., cytogenetic and physiological, can be induced at the dose rates used here.…”
Section: Discussionsupporting
confidence: 92%
“…Depending on the position in the genome at which they occur and the genetic context in which they occur, changes in DNA-methylation can have contrasting effects. Environmental stressors such as heat (Liu et al, 2018) or salinity (Al-Harrasi et al, 2018) can increase or decrease the methylation of DNA so it is not appropriate to conclude that the changes induced by IR have 'stressed' the plants in our experiments, but it seems likely that they have induced changes in gene expression and, perhaps, therefore in physiology. These changes do not seem to be associated with changes in the developmental and morphological traits measured here but are, perhaps, consistent with other genetic and physiological changes that have been reported in plants after exposure to chronic lowlevel IR.…”
Section: Dna Methylationmentioning
confidence: 90%
“…Heat-responsive DNA methylation changes in plants appear not to show a consistent trend across different species, and little is yet known about their functional role ( Liu et al, 2015 ). In Brassica rapa , heat-responsive DNA methylation was shown to be associated with differential expression of genes involved in RNA metabolic processing, and in heat stress signal transduction ( Liu et al, 2018 ). Stress signal transduction may also have been affected by the experimental methylation changes in Z .…”
Section: Discussionmentioning
confidence: 99%
“…Heat-responsive DNA methylation changes in plants appear not to show a consistent trend across different species, and little is yet known about their functional role (Liu et al, 2015). In Brassica rapa, heat-responsive DNA methylation was shown to be associated with differential expression of genes involved in RNA metabolic processing, and in heat stress signal transduction (Liu et al, 2018). Stress signal transduction may also have been affected by the experimental methylation changes in Z. marina as enriched biological processes in recovered shoots included the regulation of transmembrane transport of ions and protons (GO:0006811, GO: 0055085, GO:0006810, GO:0034220, GO:0006812, GO:0098655, GO:0098660, GO:0015672, GO:0099132, GO:0015991, GO:0098662, GO:0099131, GO:0015988, GO:1902600), and neurotransmitter levels (GO:0042133, GO0042135, GO:0001505) ( Supplementary Table S12).…”
Section: Methylome Shift Over the Course Of The Heat-stress Experimentsmentioning
confidence: 99%
“…Extensive studies have shown that dynamic changes in plant methylation levels are importantly associated with various abiotic stresses, including drought stress (Liu et al, 2018a;Sanchez & Paszkowski, 2014), cold stress (Steward et al, 2002), salt stress (Su et al, 2018;Sun et al, 2018), and ultraviolet (UV)/light radiation stresses (Eichten & Springer, 2015;Ganguly et al, 2018). In addition, DNA methylation also plays an important role in regulating growth and development Xing et al, 2015) and secondary metabolism (Bharti et al, 2015;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%